Kinematic analysis of bicycle pedalling using 2D- and 3D-motion capture systems - Garcia-Lopez, J.; Abal del Blanco, P. (ISBS Proceedings Archive (Michigan), 2017)
The main purpose was to test the validity and sensibility of two motion capture systems (sophisticated 3D vs low-cost 2D) to analyse angular kinematics during pedalling. Twelve trained cyclists participated, and were analysed in three different saddle heights at a random order: their preferred one, 2% lower and 2% higher. High correlations were found between 2D and 3D systems in all the measured variables. The 2D system was sensitive as the 3D to detect small changes in saddle height. In conclusion, the 2D motion capture system is valid and sensitive for angular kinematic analysis in the sagittal plane. It underestimated 2-3º hip and knee extensions, without differences in the ankle extension, while joint flexion were also underestimated 3-4º, 2º and 1º, respectively. Additionally, pedalling symmetry between left and right sides could be assumed.